Jurnal Kata: Iran, America and Iranian American community in firoozeh jazayeri dumas funny in farsi - Zohreh ramin, Muhammad sayyaf Jalalizadeh (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
post 9/11 th US Of America concerns the reconstuction of already demonized identities of arabs and middle eastren cultures